"Fotografija" : Individualne pozicije. - Moderna Galerija, Ljubljana (Ljubljana : Moderna galerija, 1991)
Boltanski, Christian ; Fabre, Jan ; Förg, Günther ; Kempinger, Herwig ; Molder, Jorge ; Pietroiusti, Cesare ; Schuster, Michael ; Sochacki, Paul ; Struth, Thomas
"Fotografija" : Individualne pozicije, Moderna galerija, Ljubljana, 20.12.1991 - 2.2.1992
boek